Endoscopic third ventriculostomy (ETV) for treatment of adult hydrocephalus: long-term followup with 163 patients. (3rd June 2015) - Isaacs, A; Urbaneja, G; Yong, H; Hamilton, MG
Abstract : Introduction: Treatment of specific patterns of symptomatic hydrocephalus in the adult patient may be accomplished with endoscopic third ventriculostomy (ETV) as an alternative to insertion of a ventriculoperitoneal (VP) shunt. This review examines a single center experience with ETV to treat hydrocephalus in symptomatic adult patients. Methods: Adult patients (≥18 years) with a diagnosis of hydrocephalus who were treated with ETV in Calgary between January 1994 and July 2014 were reviewed using a clinic database and registry. Results: 163 patients were identified (male=92; female=71). Mean age at the time of ETV was 46.5 years (range 18-83.4 years). 118 underwent ETV as a primary treatment and 45 patients underwent treatment after presenting with VP shunt failure (secondary ETV). 113/163 patients had a diagnosis of aqueductal stenosis, 22/163 had a diagnosis of tumor. Mean followup was 8.2 years (range 0.3-18.4 years). Symptoms in 149/163 (91.4%) of ETV patients were better or unchanged at last followup. 104/118 (88.1%) of primary ETV patients were shunt free at last followup. 39/45 (86.7%) of secondary ETV patients were shunt free at last followup. Conclusion: Endoscopic (ETV) treatment is an effective long-term treatment for a select population of adult patients with hydrocephalus.